KADAR EKSTRAKTIF SARANG SEMUT (Myrmecodia sp) DARI KABUPATEN BARITO TIMUR - Siti Hamidah; Budi Sutiya (Lambung Mangkurat University-Indonesia, 2011)
The purpose of this study was to determine the content of the Sarang Semut extractive in various parts of the plant and weight. Sarang Semut are use in the study is that weight from 0-0,9 Kg; 1-1,9 Kg; 2-2,9 Kg; 3,-3,9 Kg; 4-4,9 Kg; 5-5,9 Kg; 6-6,9 Kg; 7-7,9 Kg and taken of three parts of the plant are: base, middle and end of the plant. Analysis of data using Completely Randomized Design (CRD) 8 x 3 factorial with three replications. The result of research on cold water extraction reflects differences in average levels of extractives in each treatment. On the weight of 5-5,9 kg extractives levels average growth of 34,72% and that is the lowest extraction levels. Highest extractive content of 40,56% of the weight from 0-0,9 kg. Difference in differences in average levels of extrative produce by 5,84%. Average levels of extractives obtained by extraction of cold water which is at the base of the highest (38,83%) followed by the tip (37,74%) then the middle (35,52%). The result of research on hot water extraction showed that extraction levels are highest in the treatment of 7-7,9 kg (44%) and the smallest in treatment 4-4,9 kg (37,78%). Difference in difference of 6,62%. Hot water extraction to produce more levels of extraction from the cold water extraction. This relates to the nature of the extractive substances are more soluble at high temperatures. Extractive substances more easly dissolved and more soluble in hot water extraction than cold water extraction.Key Words : sarang semut (Myrmecodia sp), cold water extraction, hot water extraction, extractive